1988
DOI: 10.1017/s095026880005425x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal sensitivity ofClostridium botulinumtype C toxin

Abstract: SUMMARYA sterile suspension containing 950 mouse LD50 per ml of type C botulinum toxin was exposed for various periods to different temperatures. The time required for the 99% (hundred-fold) reduction of toxicity was more than 5 years at -70°C or -20°C, 6 months at + 5°C, 3 weeks at + 20°C, 2 weeks at + 28°C, 2 days at + 37°C, 9 h at +42°C, less than 30 min at +56°C, less than 20 min at + 60°C, and below 5 min at + 80 'C. The results suggest that Clostridium botulinum type C toxin, if produced in an ecosystem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…Samples tested by ELISA experienced additional cycles of freezing and thawing, bacterial overgrowth, and prolonged storage. These factors are known to decrease sample quality (Hubalek and Halouzka, 1988;Mei et al, 2001), and in some cases, samples used for ELISA were of inadequate volume (Rocke et al, 1998). Mouse inoculations performed at the NWHC to confirm ELISA results detected toxin in an additional three birds from 2004 and two birds from 2000-03 (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples tested by ELISA experienced additional cycles of freezing and thawing, bacterial overgrowth, and prolonged storage. These factors are known to decrease sample quality (Hubalek and Halouzka, 1988;Mei et al, 2001), and in some cases, samples used for ELISA were of inadequate volume (Rocke et al, 1998). Mouse inoculations performed at the NWHC to confirm ELISA results detected toxin in an additional three birds from 2004 and two birds from 2000-03 (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The possible lower prevalence of detectable toxin in samples from 2000 to 2003 might reflect loss of toxin activity during storage. Hubalek and Halouzka (1988) reported that only 6% of the toxicity of type C botulinum toxin persisted after 5 yr in storage at 220 C.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the sELISA was detecting fragments of the toxin complex that are no longer toxic. In addition, Hubálek and Halouzka (1988) demonstrated that BoNT toxicity decreased by 99 per cent after nine hours at 42°C, suggesting that the anaerobic enrichment at 40°C for five days may inactivate some of the toxin produced, leading to a negative result in the mouse bioassay. However, these explanations are somewhat speculative, and a clearer explanation of the false‐positive effect is required to improve the specificity of the assay.…”
Section: Discussionmentioning
confidence: 99%
“…It is very important to prepare samples such as serum, faecal material and feed as soon as possible for toxin detection, because of the probability of BoNT degradation before analyses. Toxins could be present in a sample at a level below the limit of detection or may have been biodegraded by microbes in the intestinal tract of the animal ( 1 ) or by exposure to high temperatures for long enough to degrade them ( 8 ). Clostridium botulinum spores are not usually present in the alimentary tract of animals; however, their detection in faecal samples collected simultaneously with the observation of botulism symptoms could indicate botulism as a probable cause of disease.…”
Section: Discussionmentioning
confidence: 99%